Pengaruh Modal, Kemampuan Manajerial, Orientasi Pelanggan, Keunggulan Bersaing Dan E-Commerce Terhadap Kinerja UMKM Di Kota Padang - Nuril Huda; Riani Sukma Wijaya (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze the influence of capital, managerial ability, customer orientation, competitive advantage and e-commerce on the perfomance of MSMEs. The location that is the object of research is MSMEs in Padang City. The data Processed is the result of distributing questionnaires to MSME players with a sample of 100 respondents. The research instrument used in this research used the likert scale method. The data analysis technique used in this research is multiple linar regression. The results of this research show that data using statistical calculations via the SPSS version 25 application shows that (1) capital has a positive and significant effect on MSME performance, (2) managerial ability has a positive and significant effect on MSME performance, (3) customer orientation has a positive effect and significant on the performance of MSMEs, (4) competitive advantage has a positive and significant effect on the perfomance of MSMEs, (5) e-commerce has a positive and significant effect on the performance of MSMEs, (6) capital, managerial ability, customer orientation, competitive advantage and e-commerce have a positive and significant effect together on the performance of MSMEs.